2016
DOI: 10.1007/s11192-016-1942-1
|View full text |Cite
|
Sign up to set email alerts
|

Bonded-communities in HantaVirus research: a research collaboration network (RCN) analysis

Abstract: Hantavirus, one of the deadliest viruses known to humans, hospitalizes tens of thousands of people each year in Asia, Europe and the Americas. Transmitted by infected rodents and their excreta, Hantavirus are identified as etiologic agents of two main types of diseases-Hemorrhagic fever with renal syndrome and hantavirus pulmonary syndrome, the latter having a fatality rate of above 40 %. Although considerable research for over two decades has been going on in this area, bibliometric studies to gauge the state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In the co-word network structure, the indicators such as degree, betweenness, closeness and modularity are measured (González-Alcaide et al, 2015;Jiandong, 2009). The degree shows the direct connection situation in the co-word network structure, and betweenness represents the capability of bringing communities (Kumar and Markscheffel, 2016). In the keyword co-word network degree, the connection of the specific keyword is represented with the other keywords in the network: more degrees show more connectivity, and it is a positive event.…”
Section: Methodsmentioning
confidence: 99%
“…In the co-word network structure, the indicators such as degree, betweenness, closeness and modularity are measured (González-Alcaide et al, 2015;Jiandong, 2009). The degree shows the direct connection situation in the co-word network structure, and betweenness represents the capability of bringing communities (Kumar and Markscheffel, 2016). In the keyword co-word network degree, the connection of the specific keyword is represented with the other keywords in the network: more degrees show more connectivity, and it is a positive event.…”
Section: Methodsmentioning
confidence: 99%
“…Other leadership skills were the ability to acquire more information and resources, integrate these into the workflow, and interact with others; personal charisma was also a quality attributed to leaders. In their study, Kumar and Markscheffel (2016) reported that the authors with the highest centrality values were often institutional heads or directors of prominent research programs. They had frequently been awarded or otherwise recognized for their research work and belonged to associations or committees of reference in their research discipline.…”
Section: Cut-points and Research Performancementioning
confidence: 99%
“…Factors that may influence this phenomenon include closer local or national ties in clinical research (González Alcaide et al 2012) or the tendency of a large part of the scientific community to investigate VAP together with other topics and lines of research. Furthermore, the largest component could be considered the seat of the main activity of a research area (Kumar and Markscheffel 2016), making membership fundamental in terms of scientific performance. Our findings support this hypothesis, both in terms of productivity and in research impact, suggesting the necessity of promoting collaboration through international multicenter studies that involve as many researchers as possible, particularly in areas outside of North American and Europe (Leydesdorff and Wagner 2008).…”
Section: Vap Co-authorship Network As a Small Worldmentioning
confidence: 99%